2019
DOI: 10.1021/acsabm.9b00523
|View full text |Cite
|
Sign up to set email alerts
|

Low-Molecular-Weight Dextran Sulfate Nanocapsules Inhibit the Adhesion of Helicobacter pylori to Gastric Cells

Abstract: The Gram-negative bacterium Helicobacter pylori is the most common bacterial pathogen in humans, infecting 24-79% of the population at any time. Standard eradication protocols involve multi-target therapy including combinations of antibiotics, which has promoted the emergence of resistant strains. To address this challenge, we prepared antibiotic-free colloidal nanoparticles designed to interfere with the adhesion mechanisms of H. pylori and thus prevent both the onset and recurrence of infection. Our colloida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 72 publications
0
2
0
Order By: Relevance
“…On the other hand, antiadhesive treatment could prevent new infections or recurrence, which is still a big problem in H. pylori clinical treatment, even after positive eradication therapy. For this, new strategies and targets should be considered, using innovative formulations, which increase the residence time of the antibacterial drug cargo in the stomach by interaction with the mucus layer, specifically interacting with bacterial virulence factors (Menchicchi et al 2019). Previous studies have shown that both anionic polysaccharides such as dextran sulfate and cationic ones such as chitosan can interact with mucins (Menchicchi et al 2015a) and some of these can also modulate adhesive interactions with H. pylori (Menchicchi et al 2015b).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, antiadhesive treatment could prevent new infections or recurrence, which is still a big problem in H. pylori clinical treatment, even after positive eradication therapy. For this, new strategies and targets should be considered, using innovative formulations, which increase the residence time of the antibacterial drug cargo in the stomach by interaction with the mucus layer, specifically interacting with bacterial virulence factors (Menchicchi et al 2019). Previous studies have shown that both anionic polysaccharides such as dextran sulfate and cationic ones such as chitosan can interact with mucins (Menchicchi et al 2015a) and some of these can also modulate adhesive interactions with H. pylori (Menchicchi et al 2015b).…”
Section: Introductionmentioning
confidence: 99%
“…Alternative therapies to overcome these challenges have been comprehensively explored [15][16][17][18]. Focus has been given to understanding bacterial infection mechanisms and interaction with the host [19,20], identifying bacterial specific molecules that may represent potential targets, such as bacterial virulence factors, urease, flagella or surface adhesins [21][22][23]. The combination of these targets with improved encapsulation systems for local delivery of antibiotics (using micro-or nano-systems) [24][25][26][27][28][29][30][31][32][33], usage of compounds from natural sources [34][35][36][37][38][39][40][41] or vaccination [42][43][44][45] has allowed the development of more precise and efficient systems aiming H. pylori eradication.…”
Section: Introductionmentioning
confidence: 99%